PHYSICAL THERAPY OF PERSONS WITH CENTRAL FORM OF ANKYLOSING SPONDYLITIS (Physical Culture and Sport: Scientific Perspective, 2024)
Ankylosing spondylitis is a chronic progressive inflammatory disease of the joints with a predominant lesion of the axial skeleton. The prevalence of the disease is 0.05-0.1%. Many concomitant disorders are associated with ankylosing spondylitis: chronic pain, functional disturbances of vision and cardiac conduction, apathy, weight loss, etc. But the correct selection of the course of treatment, physical exercises and physiotherapeutic methods will minimize the intensity of pain and reduce the dose of painkillers. Physical therapy for AS is aimed at improving and maintaining spinal flexibility and normal posture, relieving symptoms, reducing functional limitations, and minimizing complications. The purpose of the study: to analyze literary sources and scientific articles to familiarize with the peculiarities of the impact of methods and means of physical rehabilitation aimed at alleviating the symptoms of AS and maintaining the quality of life of patients.. Research methods. Systematization and analysis of scientific and methodological literature in order to assess the impact of physiotherapeutic methods on alleviating the symptoms of ankylosing spondylitis. Work results. The general scientific approach to the physical therapy of patients with ankylosing spondylitis is based on massages, breathing exercises, special diets, etc. included in the rehabilitation plan. In addition, it is necessary to constantly monitor the results of research on the treatment and prevention of AS in order to improve rehabilitation programs. Physical therapy should be aimed at minimizing the impact of pain centers. Conclusions. Thus, physical therapy plays an important role in the treatment of AS. It is aimed not only at improving the flexibility of the spine, alleviating symptoms, reducing functional limitations and preventing complications, but also at improving the psycho-emotional state of the patient.
Keywords: physical therapy; methods of treatment of ankylosing spondylitis; Bekhterev's disease